Actuarial Aspects in Life Insurance - Muhammad Risalah; Nur Ahmadi Bi Rahmani (Penerbit Jurnal Indonesia, 2022)
The emergence of various syriah financial institutions (banks and non-banks) shows us that people are increasingly trusting in the sharia system. In connection with the number of financial institutions such as sharia insurance, both general and life insurance, it provides a lot of job opportunities. Therefore, it is necessary to have good quality human resources (HR). Human resources are an important element in a company, because this element is the part that drives the system in a company in order to achieve company goals. Insurance companies, both general and life itself, cannot be separated from the performance of actuaries. This type of research is descriptive with a qualitative approach. Data collection used by using interviews, study documentation and observation. The study in this research is to find out